Efficient Synthesis Of Alkyl And Aryl 2,3-Unsaturated Glycopyranosides via Ferrier Rearrangement - Dayang Halimatulzahrah, bt. Abang Kamaluddin; Zainab, Ngaini (1112-9867, 2011)
The reactions of 3,4,6-tri-O-acetyl-D-glucal with phenolic and aliphatic alcohol in various Lewis acid catalysts (namely La(NO3)3.6H2O, InCl3, ZnCl2 and BF3•OEt2) have furnished the corresponding alkyl and aryl 2,3-unsaturated glycopyranosides via Ferrier rearrangement. BF3•OEt2 showed the best Lewis acids catalysts with excellent yields and minimum reaction times. The reactions performed in CH3CN gave better yields and shorter reaction times compared to CH2Cl2. The electron withdrawing properties of aromatic ring resulting lower yields of aryl 2,3-unsaturated glycopyranosides compared to alkyl 2,3-unsaturated glycopyranosides under this condition. This study is significant in the preparation of O-glycosides via Ferrier rearrangement